THE DOUBLE-EDGED SWORD - SEVERE HYPOPHOSPHATEMIA POST INTRAVENOUS BISPHOSPHANATE FOR SEVERE REFRACTORY HYPERTHYROID-INDUCED HYPERCALCEMIA: A CASE REPORT - T, Suguneisvari; MM, Nur Hidayah; R, Subashini (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Severe hypophosphatemia, defined as serum phosphate levels of <1 mg/dl (0.32 mmol/L), after intravenous bisphosphonate is a rare occurrence. It can lead to rhabdomyolysis, respiratory failure, convulsions and arrhythmias if not detected and treated early. Few reported cases of bisphosphonate-induced hypophosphatemia are related to malignancy-induced hypercalcemia or osteoporosis treatment. We present a case of severe hypophosphatemia post intravenous zoledronic acid for hyperthyroid-induced refractory severe hypercalcemia. CASE A 62-year-old female presented with thyrotoxicosis (weight loss, palpitation, heat intolerance) for 5 months. On physical examination, she had hand tremors, proximal myopathy and tachycardia with multinodular goitre. Other systemic examinations were normal. She was biochemically hyperthyroid (TSH: <0.01 m IU/L, FT: 467 pmol/L). Serum PTH was suppressed (0.59 mmol/L). Initial corrected calcium was 3.5 mmol/L with phosphate of 0.72 mmol/L. Intravenous zoledronic acid 4 mg was administered as she did not respond to hyperhydration. After 48-hours, repeat serum phosphate was 0.22 mmol/L with low calculated renal-tubular-reabsorption-ofphosphate (TMP/GFR) [0.41 mmol/L] indicating renal phosphate wasting. Repeat serum PTH level was normal (4.35 mmol/L), corrected calcium was 2.01 mmol/L with low 25-OH vitamin D level (<7.5 nmol/L). A CT TAP done showed no evidence of malignancy. All her tumour markers were negative. Biopsy of thyroid nodules were negative for malignancy. CONCLUSION Based on previous case reports, bisphosphonate-induced hypophosphatemia is postulated to be a result of secondary hyperparathyroidism (drug-induced) causing severe hypophosphatemia through renal-phosphate wasting. One of the risk factors that can precipitate this is vitamin D deficiency. In our case, the slightly elevated PTH level post bisphosphonate coupled with reduced TMP/GFR level support the diagnosis of bisphosphonate-induced severe hypophosphatemia. Removal of the offending drug is the mainstay of treatment in drug-induced hypophosphatemia. Asymptomatic, mild to moderate hypophosphatemia is being treated with oral phosphate whereas severe symptomatic hypophosphatemia is being given intravenous phosphate. It may also be prevented with vitamin D and calcium supplements.